MR Imaging of the Lumbosacral Plexus: A Review of Techniques and Pathologies. Issue 5 (1st May 2015) - Neufeld, Ethan A.; Shen, Peter Yi; Nidecker, Anna E.; Runner, Gabriel; Bateni, Cyrus; Tse, Gary; Chin, Cynthia
ABSTRACT The lumbosacral plexus is a complex anatomic area that serves as the conduit of innervation and sensory information to and from the lower extremities. It is formed by the ventral rami of the lumbar and sacral spine which then combine into larger nerves serving the pelvis and lower extremities. It can be a source of severe disability and morbidity for patients when afflicted with pathology. Patients may experience motor weakness, sensory loss, and/or debilitating pain. Primary neurologic processes can affect the lumbosacral plexus in both genetic and acquired conditions and typically affect the plexus and nerves symmetrically. Additionally, its unique relationship to the pelvic musculature and viscera render it vulnerable to trauma, infection, and malignancy. Such conditions are typically proceeded by a known history of trauma or established pelvic malignancy or infection. Magnetic resonance imaging is an invaluable tool for evaluation of the lumbosacral plexus due to its anatomic detail and sensitivity to pathologic changes. It can identify the cause for disability, indicate prognosis for improvement, and be a tool for delivery of interventions. Knowledge of proper MR protocols and imaging features is key for appropriate and timely diagnosis. Here we discuss the relevant anatomy of the lumbosacral plexus, appropriate imaging techniques for its evaluation, and discuss the variety of pathologies that may afflict it.